The Polish crawling peg system: A cointegration analysis - Carsten Trenkler (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
After a temporary period of a fixed exchange rate regime pegging the Polish zloty to the U.S. dollar, Poland established a preannounced crawling peg regime on October 15, 1991. In this system the zloty is tied to a currency basket and devalued with a preannounced monthly rate (rate of crawl). If the monetary authorities have been successful in defending the crawling peg stable long-run relationships between the Polish zloty on the one hand and the basket's value and the currencies comprising the basket on the other hand are expected to exist. I test for such long-run relationships within the cointegration framework. However, as the transition path of the Polish exchange rate was not; smooth due to discrete steep devaluations one has to apply cointegration tests taking such structural shifts into account. Using recently developed test procedures I find the postulated cointegration relations and conclude that the monetary authorities could defend the crawling peg for the sample period under study.
urn:nbn:de:kobv:11-10047970
Keywords: 330